National Standards of Education - Hikmah Hikmah (Indonesian Journal of Education (INJOE), 2022)
National education standards are minimum criteria regarding various relevant aspects in the implementation of the national education system and must be met by education providers and/or units throughout the jurisdiction of the Unitary State of the Republic of Indonesia. National education standards are minimum standards or criteria related to the education system held in Indonesia. National Education is used for Education organized by the Central Government, Local Government, and the community in the formal education pathway, non-formal education pathway, and informal education pathway. The formal education pathway is formal early childhood education; basic education; middle education; and higher education. The non- formal  education  pathway  is  non-formal  early  childhood education; and equality education